KORELASI ANTARA CARA BELAJAR DAN PERHATIAN ORANG TUA DENGAN PRESTASI BELAJAR KEJURUAN OTOMOTIF SISWA KELAS X PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN SMK MUHAMMADIYAH I BAMBANGLIPURO BANTUL YOGYAKARTA TAHUN AJARAN 2014/2015 - Catur Budi Santoso; Suparmin Suparmin (Jurnal Taman Vokasi, 2015)
This study aimed to describe (1) correlation between learning ways with learning achievement of automotive vocational; (2) correlation between parents’ attention with learning achievement of automotive vocational; and (3) correlation between learning ways and parents’ attention with learning achievement of automotive vocational among the tenth grade students of SMK Muhammadiyah 1 Bambanglipuro Bantul Yogyakarta in academic year 2014/2015. The type of this study was ex-post facto. Data collecting techniques used questionnaires and documentation. Data analyzing techniques used descriptive analysis and hypothesis testing used double regression with two predictors. This study shows that (1) there was a positive and significant correlation between learning ways with learning achievement of automotive vocational with the score of significance 0.000 < 0.05; (2) there was a positive and significant correlation between parents’ attention with learning achievement of automotive vocational with the score of significance 0.000 < 0.05; and (3) there was a positive and significant correlation between learning ways and parents’ attention with learning achievement of automotive vocational among the tenth grade students of SMK Muhammadiyah 1 Bambanglipuro Bantul Yogyakarta in academic year 2014/2015 with the score of significance 0.000 < 0.05. The score of determinant coefficient (R2) was 0.320, it means that learning ways and parents’ attention gave positive contribution 32% toward learning achievement of automotive vocational, while 68% was influenced by other factors that were not discussed in this study.